We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
77
1
avatar+87 

Given f(x) = 2x^2 +3x and g(x) = 5x^2 -2x-6 

what is (f+g) (x)

A. -3x^2 + 5x+6 

B. 7x^2 + X -6 

C. 10x^2 + X +6

D.3x^2 -5x-6 

 Mar 14, 2019
 #1
avatar+101086 
0

f(x) = 2x^2 +3x and g(x) = 5x^2 -2x-6 

 

(f + g) (x)  means   f(x) + g(x)  =  [ 2x^2 + 3x ] + [ 5x^2 - 2x - 6 ]  =  7x^2 + x - 6

 

 

cool cool cool

 Mar 14, 2019

5 Online Users